La producción de café y su influencia en el nivel de ingresos de los socios de la organización Procap del cantón Puyango provincia de Loja periodo 2010-2013 - Granda Córdova, Ridín Manuel (2015)
The investigation "The production of coffee and their influence in the level of the partners' of the organization income PROCAP of the canton Puyango province of Loja period 2010-2013", it was developed with the general following objective: To analyze the production of coffee and their incidence in the level of income of the associate producers in the organization PROCAP of the canton Puyango province of Loja in the period 2010 -2013. The production of coffee has suffered strong impacts during the production processes, to this adds the volatility of the prices that you have its direct influence in the income of those producing of coffee, situation that is summarized in the following problem: "The production and prices of the coffee have influence in the level of the partners' of the organization profits PROCAP, and I get in the earnings of the coffee" sector. The investigation is of descriptive type and of field, it was used scientific methods: Inductive-deductive method, the analysis method and synthesis, the statistical method; also, the technique of the observation, and the survey was used applied relating partners of the association PROCAP. It was determined that the partners of the association PROCAP, located in the canton Puyango of the Loja province, carry out the agricultural activities in small production (UPAs) units, in these UPAs, they have their properties of coffee. The production of coffee soon after the year 2011, where the roya attacked its coffee plantations drastically, it fell in significant way whose influence is reflected in the fall of the income and the considerable losses at the end of the economic exercise. Key words: production of coffee, price of coffee, production costs, income, PROCAP, Puyango.